Ultraviolet-Ozone Treatment: An Effective Method for Fine-Tuning Optical and Electrical Properties of Suspended and Substrate-Supported MoS2 - Fahrettin Sarcan; Alex J. Armstrong; Yusuf K. Bostan; Esra Kus; Keith P. McKenna; Ayse Erol; Yue Wang (Nanomaterials, 2023)
Ultraviolet-ozone (UV-O3) treatment is a simple but effective technique for surface cleaning, surface sterilization, doping, and oxidation, and is applicable to a wide range of materials. In this study, we investigated how UV-O3 treatment affects the optical and electrical properties of molybdenum disulfide (MoS2), with and without the presence of a dielectric substrate. We performed detailed photoluminescence (PL) measurements on 1–7 layers of MoS2 with up to 8 min of UV-O3 exposure. Density functional theory (DFT) calculations were carried out to provide insight into oxygen-MoS2 interaction mechanisms. Our results showed that the influence of UV-O3 treatment on PL depends on whether the substrate is present, as well as the number of layers. Additionally, 4 min of UV-O3 treatment was found to be optimal to produce p-type MoS2, while maintaining above 80% of the PL intensity and the emission wavelength, compared to pristine flakes (intrinsically n-type). UV-O3 treatment for more than 6 min not only caused a reduction in the electron density but also deteriorated the hole-dominated transport. It is revealed that the substrate plays a critical role in the manipulation of the electrical and optical properties of MoS2, which should be considered in future device fabrication and applications.